The Relationship Between Ultra-Processed Food Consumption Patterns and the Nutritional Status of Adolescents in Urban Areas - Renita Afriza; Andrafikar (Miracle Journal Get Press, 2025)
The present study aims to examine in depth the relationship between consumption patterns of ultra-processed foodstuffs and the nutritional status of adolescents in urban areas. The present study employed a quantitative analytical design, adopting a cross-sectional approach. The collection of data was conducted utilising a validated Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ). Additionally, secondary data were collected pertaining to demographic characteristics (age, gender, and socioeconomic status) and physical activity levels, which were measured using the Physical Activity Questionnaire for Adolescents (PAQ-A). The results indicated a positive correlation between the frequency of UPF consumption and the proportion of adolescents who were overweight or obese. The ingestion of UPF at a rate of four times per day has been shown to increase the risk of overnutrition or obesity by 2.85-fold (p = 0.000). Concurrently, a lack of physical activity has been demonstrated to increase the risk by 2.4-fold. The present findings underscore the significance of regulations and public policies in the control of the distribution and promotion of ultra-processed foods, with particular reference to the vulnerability of adolescents to the influence of unhealthy food environments.